Variations in experience of social support and physical health among adult residents of Poland in urban versus rural areas - Bożena Moskalewicz; Paweł Goryński; Jakub Stokwiszewski; Jacek Moskalewicz; Andrzej Kiejna; Bogdan Wojtyniak (National Institute of Public Health - National Institute of Hygiene, 2019)
Background. A study reveals - against to common beliefs -less support between rural area residents in comparison to town-dwellers and significantly higher support for healthy, not for poor health research participants. Objectives. The aim of our paper was comparing support from spouse/partner, relatives, friends and strangers among people with good and ill physical health. A next purpose was to find differences of social support and experience of social undermining in urban and rural residential settings. Material and methods. The study "Epidemiology of Mental Disorders and Access to Mental Health Care, EZOP - Poland" was carried out on random sample of 24 000 of Poland residents and a 50,4% response rate, 10 081 computerassisted personal interviews. Of those respondents, 4 000 constituted a sub-sample asked to complete the social networks and support section of the questionnaire. Data were analyzed by age, gender, residential setting and marital status for statistically significant differences in the percentage of functional and structural social support being reported, using the chi-squared test with a significance level of 0.05 used to reject the null hypothesis (H0 = lack of relationship between variables). Results. A majority of respondents maintain that in difficult life situations, family and a close network of friends and acquaintances make it possible to openly discuss problems and obtain help. However, respondents who rate their health as "poor" or "very poor" significantly less often than healthy individuals experience support coming from their relatives, friends, or strangers. In comparison to urban areas, the extent of social support in rural areas is significantly limited. The rural setting offers less support and even less opportunities for interaction with relatives, friends, acquaintances and strangers. Negative social factors- low levels of trust, isolation from friends and family, lack of a social life, lack of a helpful neighborhood - are conditions significantly more often found in the countryside than in urban areas. Conclusions. Results obtained from the EZOP study shows that amount of social support received is higher in urban areas and among those who enjoy better physical health.